PROFESIONAL GURU PROFESIONAL GURU DALAM MENGHADAPI TANTANGAN PERKEMBANGAN TEKNOLOGI PENDIDIKAN: MENINGKATKAN KOMPETENSI GURU UNTUK MENGHADAPI TANTANGAN TEKNOLOGI DALAM PENDIDIKAN - devitriana, idanyoman; Jaya, I Gede Tresna; Pramana, Ida Bagus Kade Yoga (UHN IGB Sugriwa Denpasar, 2025)
This journal discusses the role and challenges faced by teachers in improving the quality of education in the digital era. Education is recognized as the key to achieving a better life, where teacher competence is a crucial factor in achieving learning goals. With the development of information technology, teachers are required to have digital pedagogical skills to utilize technology in the teaching process. This research uses a qualitative approach, collecting data through interviews, observation and documentation to explore how teachers face these challenges. The research results show that teacher professionalism must continue to be improved in order to adapt to curriculum changes and technological developments. The challenges faced include the need to update skills, face scientific advances, and act as a facilitator and motivator. The proposed solutions include empowering teachers in the use of technology and increasing abilities in using modern learning tools. This journal emphasizes the importance of human resource readiness and supporting facilities and infrastructure to achieve effective technology-based education. Keywords: Teacher Professionals, Challenges, Educational Technology